Boosting Low-Valent Aluminum(I) Reactivity with a Potassium Reagent - Grams, Samuel; Eyselein, Jonathan; Langer, Jens; Färber, Christian; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
The reagent RK [R=CH(SiMe3)2 or N(SiMe3)2] was expected to react with the low-valent (DIPPBDI)Al (DIPPBDI=HC[C(Me)N(DIPP)]2, DIPP=2,6-iPr-phenyl) to give [(DIPPBDI)AlR]−K+. However, deprotonation of the Me group in the ligand backbone was observed and [H2C=C(N-DIPP)−C(H)=C(Me)−N−DIPP]Al−K+ (1) crystallized as a bright-yellow product (73 %). Like most anionic AlI complexes, 1 forms a dimer in which formally negatively charged Al centers are bridged by K+ ions, showing strong K+⋅⋅⋅DIPP interactions. The rather short Al–K bonds [3.499(1)–3.588(1) Å] indicate tight bonding of the dimer. According to DOSY NMR analysis, 1 is dimeric in C6H6 and monomeric in THF, but slowly reacts with both solvents. In reaction with C6H6, two C−H bond activations are observed and a product with a para-phenylene moiety was exclusively isolated. DFT calculations confirm that the Al center in 1 is more reactive than that in (DIPPBDI)Al. Calculations show that both AlI and K+ work in concert and determines the reactivity of 1.
CRIS-Team Scopus Importer:2020-07-10
Keywords: aluminum; C−H activation; density-functional calculations; low-valent complexes; potassium